Foreign Aid and Economic Growth in Egypt: A Cointegration Analysis - Ali, Hoda Abd el Hamid (International Journal of Economics and Financial Issues, 2013)
<!--[if gte mso 9]> <![endif]--> <p class="MsoNormal" style="margin-bottom: .0001pt; text-align: justify; text-justify: inter-ideograph; line-height: normal; mso-layout-grid-align: none; text-autospace: none; direction: ltr; unicode-bidi: embed;">There is a current and growing debate on the effectiveness of foreign aid, especially in Egypt, as the country is going through a critical period in its transition to democracy. The obvious question is to what extent foreign aid to Egypt will be effective in promoting economic growth. By using Johansen Cointegration test and Vector Error Correction Model (VECM), the paper finds a negative and significant impact of foreign aid on economic growth in the long and short run. It is highly suggested that Egypt must rely upon the indigenous resources to promote development rather depending on external factors. Keywords: Economic Growth; Foreign Aid; Johansen Cointegration Test; Vector Error Correction Model; Egypt JEL Classifications: F3; F35; 01 <!--[if gte mso 9]> Normal 0 false false false EN-US X-NONE AR-SA <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <![endif]-->